Primary Central Nervous System Lymphoma with Peripheral Nerve Involvement: Case Report - Mori, Yoshimasa (Cureus, 2019)
A 50-year-old man presented with dizziness and hearing disturbance in the right ear. Magnetic resonance imaging (MRI) revealed a well-enhanced mass lesion in the right cerebellopontine (CP) angle that appeared to originate in the cerebellum. A surgical specimen obtained at the subtotal resection with craniotomy revealed a diffuse large B-cell lymphoma (DLBCL). During the three courses of chemotherapy with high-dose methotrexate (MTX) with leucovorin rescue, he developed a right abducens palsy, left oculomotor palsy, left facial palsy, right trigeminal sensory disturbance, and paraparesis. Although the brain MRI showed that the CP angle tumor had disappeared completely following chemotherapy, enhanced lesions along the cauda equina were detected on a lumbar spine MRI. FDG-PET (18 F-fluorodeoxyglucose positron emission tomography) revealed multiple high-uptake abnormalities in the cranial nerves and spinal nerves. Tumor cells were found in the cerebrospinal fluid specimen from a lumbar puncture. Craniospinal irradiation was performed, including all the abnormal FDG high-uptake areas, and was effective in relieving the patient’s symptoms. On FDG-PET, the high-uptake abnormalities in the peripheral nerves disappeared. However, five weeks after the irradiation, he developed right trigeminal sensory disturbance, hoarseness, dysphagia, and right arm pain. FDG-PET disclosed multiple high-uptake abnormalities in more peripheral portions of the cranial nerves and spinal nerves. Chemotherapy with rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine (Oncovin®), and prednisolone (R-CHOP) was then resorted to which mitigated his symptoms. On follow-up FDG-PET, the high-uptake abnormalities in the peripheral nerves disappeared again.